Early risk prediction in idiopathic versus connective tissue disease-associated pulmonary arterial hypertension: call for a refined assessment. Issue 3 (2nd August 2021) - Hjalmarsson, Clara; Kjellström, Barbro; Jansson, Kjell; Nisell, Magnus; Kylhammar, David; Kavianipour, Mohammad; Rådegran, Göran; Söderberg, Stefan; Wikström, Gerhard; Wuttge, Dirk M.; Hesselstrand, Roger
Despite systematic screening and improved treatment strategies, the prognosis remains worse in patients with connective tissue disease-associated pulmonary arterial hypertension (CTD-PAH) compared to patients with idiopathic/hereditary pulmonary arterial hypertension (IPAH). We aimed to investigate differences in clinical characteristics, outcome and performance of the European Society of Cardiology (ESC)/ European Respiratory Society (ERS) risk stratification tool in these patient groups.  This retrospective analysis included incident patients with CTD-PAH (n=197, of which 64 had interstitial lung disease, ILD) or IPAH (n=305) enrolled in the Swedish PAH Register (SPAHR) 2008–2019. Patients were classified as low, intermediate or high risk at baseline, according to the "SPAHR-equation". One-year survival, stratified by type of PAH, was investigated by Cox proportional regression.  At baseline, CTD-PAH patients had lower diffusing capacity for carbon monoxide and lower haemoglobin but, at the same time, lower N-terminal prohormone-brain natriuretic peptide, longer 6 min walk distance, better haemodynamics and more often a low-risk profile. No difference in age, World Health Organisation functional class (WHO-FC) or renal function between groups was found. One-year survival rates were 75, 82 and 83% in patients with CTD-PAH with ILD, CTD-PAH without ILD and IPAH, respectively. The 1-year mortality rates for low-, intermediate- and high-risk groups in the whole cohort were 0, 18 and 34% (p<0.001), respectively. Corresponding percentages for CTD-PAH with ILD, CTD-PAH without ILD and IPAH patients were: 0, 26, 67% (p=0.008); 0, 19, 39% (p=0.004); and 0, 16, 29% (p=0.001), respectively.  The ESC/ERS risk assessment tool accurately identified low-risk patients but underestimated the 1-year mortality rate of CTD-PAH and IPAH patients assessed as having intermediate risk at diagnosis. ESC/ERS risk assessment accurately identifies low-risk patients but underestimates the 1-year mortality rate of CTD-PAH and IPAH patients assessed as having intermediate risk at diagnosis https://bit.ly/3dDl5x8